Design and Analysis of a Rectangular Fin with Comparing by Varying Its Geometry and Material, With Perforation and Extension - et. al., Kota Leela Sai Bharath , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Extending fins improve the rate of heat transfer or decrease convection. A fin is only for the reason of increasing the surface area in order to maximize heat transmission like a motor, heat exchanger, CPU, or to a heat-generating surface area. The benefit of performing thermal analysis on a flat fin is that it will tell how far heat is dissipated. This paper's primary purpose is to design and evaluate the thermal properties of rectanglular fin with varying geometry and content, and to expand the rectangular fin plate with Catia5R tools. Catia and Ansys are used to construct the geometries, and analyses of thermal properties are applied to them The tip is 5mm wide at present, decreased to 4mm. The aluminum alloy used in the manufacture of the rectangular fin body has thermal conductivity of 110-160 mK. The conducting coating on this paper is replaced with Aluminum Alloy 1100, which has a thermal conductivity of 210 to the mW/mk for the substrate and many unusual and prolonged margins. Case studies are used and graphed as well as total conclusions are drawn.